2002
DOI: 10.1034/j.1600-0722.2002.21367.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal uptake of mercury from lined amalgam restorations in guinea pigs

Abstract: The aim of the present study was to examine pulp in amalgam-restored teeth of guinea pigs with respect to the presence of mercury, and to evaluate whether lining of cavities with resin modified glass ionomer cements had any effect on the penetration of mercury. Class V cavities were prepared in 63 incisor teeth of 21 guinea pigs. Three amalgam restorations were placed per animal, one without base liner and two with different resin-modified glass ionomer cements (GC Lining LC and Ionoseal). Following observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…[ 19 ] and Akyüz et al . [ 20 ] but is in agreement with studies done by Kurosaki and Fusayama[ 4 ] who stated that mercury could not be found inside dentin tubules, but rather it returns to the amalgam structure and reacts with the unreacted alloy core.…”
Section: Discussionsupporting
confidence: 90%
“…[ 19 ] and Akyüz et al . [ 20 ] but is in agreement with studies done by Kurosaki and Fusayama[ 4 ] who stated that mercury could not be found inside dentin tubules, but rather it returns to the amalgam structure and reacts with the unreacted alloy core.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of resin cement linings on the pulpal uptake of Hg from amalgam restorations was investigated by Akyuz and Calgar. 168 Cavities were created in the incisor teeth of guinea pigs and lined with either conventional liners or resin modified glass cements prior to restoration with Hg amalgam. Restored teeth were extracted after 1, 7 or 30 days and the Hg concentration in dental pulp determined using AAS.…”
Section: 812mentioning
confidence: 99%